Polymorphism of MUC1 Gene in Vietnamese Gastric Cancer Patients: A Multicenter Case–Control Study - Nguyen, Ngoc-Lan Thi; Dang, Ngoc-Dzung Thi; Dang, Quang-Huy; Tran, Van-Chuc; Vo, Hoang-Long; Yamaguchi, Masamitsu; Ta, Thanh-Van (Frontiers in Oncology, 2021)
Background: A few studies revealed the polymorphisms of the Mucin 1 gene have a role and significance as a susceptible factor contributing to gastric cancer. To better understand the roles of two MUC1 genotype polymorphisms of rs4072037 and rs2070803 in the development of gastric cancer in Vietnamese population, a multi-center, large-sample, case-control study was conducted to investigate the potential association of these single-nucleotide polymorphisms of the MUC1 gene with gastric cancer risk and to evaluate the combination factors in relation with these single-nucleotide polymorphisms. Methods: This case-control study included 302 gastric cancer patients and 304 controls at four national medical hospitals between 2016 and 2018. All participants were interviewed for social-demographic characteristics, smoking and drinking status, and personal and family history of gastric diseases. Genotyping was done using polymerase chain reaction-restriction fragment length polymorphism analysis. The association of Single Nucleotide Polymorphisms with gastric cancer was explored using logistic regression models. Results: AA genotype for rs4072037 was significantly associated with increased gastric cancer. Those with AA genotype had higher gastric cancer risk compared to patients with AG (OR: 2.09, 95% CI: 1.48–2.96) and a combination of AG+GG (OR: 1.85, 95% CI: 1.33–2.56). In rs2070803, GG genotype increased gastric cancer risk when be compared with AG (OR: 1.97, 95% CI: 1.39–2.80) and AG+AA (OR: 1.71, 95% CI: 1.23–2.39). AG genotypes in both SNP decreased gastric cancer risk when compared with homogenous genotype, more specifically AA (OR: 0.51, 95% CI: 0.35–0.72) and GG (OR: 0.58, 95% CI: 0.35–0.97). These genotypes in combination with above-60-year-old age, male gender, alcoholism and personal history of gastric disease were also significantly elevated risk factors for gastric cancer. Conclusions: rs4072037 and rs2070803 of Mucin 1 genes are two genotypic risk factors for gastric cancer. Those in combination with gender, family history, smoking and drinking habits significantly increase the risk of gastric cancer.